Viuria Grishin, 2019 (Lepidoptera: Hesperiidae): taxonomy, description of two new species, and remarks on the morphology of secondary sexual organs of males - Siewert, Ricardo Russo; Lemes, José Ricardo Assmann; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (European Journal of Taxonomy, 2023)
The taxonomy of the Neotropical Carcharodini genus Viuria Grishin, 2019 (Lepidoptera: Hesperiidae: Pyrginae) is presented. Two new species are described: Viuria inanna sp. nov. from south-southeastern habitats Brazil and Paraguay, and Viuria acadia sp. nov. from Brazil and Ecuador. Illustrations of adults, including morphology of secondary sexual organs in males, male and female genitalia, diagnoses, remarks, and updated geographical distributions are also provided for all species.